Impact of Built Environment and Neighborhood on Promoting Mental Health, Well-being, and Social Participation in Older People: an Umbrella Review - Bonaccorsi, G.; Milani, C.; Giorgetti, D.; Setola, N.; Naldi, E.; Manzi, F.; Del Riccio, M.; Dellisanti, C.; Lorini, C. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The built environment, especially in the context of the neighborhood, affects older people’s health. This umbrella review aims to summarize the associations between factors and interventions in the built environment as regards modifying or improving mental health, well-being, social inclusion and participation in the elderly. Methods. We searched articles in the following databases: PubMed, Embase, Cochrane Library, Scopus, Avery Index, Sage, Web of Science, Health Evidence, and Google Scholar, without any time limits. The factors and interventions examined have been classified into three categories (urban infrastructure, green infrastructure, built environment), and we have assessed their relationships with each of the health outcomes. Results. Eight reviews have been included. The results show a positive association between factors and interventions and health outcomes, even though this tends to differ with respect to some of the elements (study design, sample size, built environment and health outcome measurements, and the quality of the primary studies included in the reviews) in the selected studies. Conclusions. In conclusion, the present study suggests and confirms that acting on the built environment has a positive impact on mental health and social inclusion.